(untitled) (Journal of Parents and Teachers, 2014)
The participation of families in the early educational stages is essential for the correct development of their children, which is why an active and continuous collaboration of teachers and parents is necessary. Through this article, a proposal for guidance and support to families with children in Early Childhood Education is presented. To do this, a program intervention model was proposed whose main objective was to get parents to know their sons and daughters better and to become involved and integrated in school. Different activities and talks were held, and extensive information and observation material was provided.